(untitled) (Journal of Nematode Morphology and Systematics, 2010)
Within the Bursaphelencus sexdentati group, differentiation of species is mainly based on the shape of the female tail and the male spicules. In this study, ITS1/2 sequences of 17 isolates belonging to five species of the ‘sexdentati’ group (B. sexdentati, B. vallesianus, B. pinophilus, B. poligraphi, B. borealis) and of two B. eggersi isolates were obtained. In some isolates of B. sexdentati, sequence heterogeneity at a few sites of ITS2 was detected. Cluster analysis of genetic distances between isolates of the ‘sexdentati’, ‘eggersi’ and ‘xylophilus’ groups confirmed their morphological affiliation to the respective species and species groups. In addition, isolates of B. sexdentati were separated into two sub-clusters suggesting the existence of a Central European and a South European type of this species or even two separate species. This was supported by morphological studies showing the differences in shape of female tail and male spicules between the two types.